Inclusive Education for Children with Disabilities in India: Legal Analysis under the Rights of Persons with Disabilities Act, 2016 - Kukreja, Ritika; Thakur, Sheetal; Dadwal, Lalit (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
Inclusive education for children with disabilities continues to be an essential but insufficiently fulfilled requirement within India's educational system. The Rights of Persons with Disabilities Act (RPWD), 2016, signifies a significant transition from a welfare-focused to a rights-oriented framework, clearly acknowledging inclusive education as a basic right. This study conducts a doctrinal legal examination of the (RPWD) Act, 2016, focusing on its main provisions concerning education, their relationship with the Right to Education Act, 2009, and related judicial interpretations. It evaluates the difficulties in implementation and the discrepancies between the law's purpose and actual situations. By analyzing constitutional requirements, legal frameworks, and significant court rulings, the research assesses the effectiveness of the Act in fostering equal and high-quality inclusive education. The document ends with suggestions for reforms in legal, institutional, and educational areas to close the current gap and fulfil the constitutional commitment to inclusive education for every child in India.